Predictability of salvage and outcome of Gustilo and Anderson type-IIIA and type-IIIB open tibial fractures using Ganga Hospital Scoring system. Issue 2 (February 2015) - Madhuchandra, P.; Rafi, Mohammed; Devadoss, Sathish; Devadoss, A.
Abstract Although numerous scoring systems are designed for lower limb open injuries, most of them are based on orthopaedic and vascular injuries and can define only an amputation score. These scoring system lack specificity and sensitivity in predicting the salvage and outcome. Ganga Hospital Scoring system was found to have good specificity in predicting the outcome in Gustilo type-IIIA and type-IIIB injuries. We have validated in our study the Ganga Hospital Scoring system which grades the open injuries based on severity of injury to covering structures, functional and the skeletal units. The score was validated in 40 open injuries of tibia, 11 type-IIIA and 29 type-IIIB. Predictability of salvage and outcome was measured based on this scoring system. Results of our study correlated well with outcome of Ganga hospital study. 38 of 40 limbs with score below 14 and 1 with score above 14 were salvaged. The sensitivity and specificity for the threshold score of 14 was 100% and 95% respectively. Requirement of flaps, number of surgical procedures, time to bony union and infection rates in different groups were similar to original study. The Ganga scoring system was found to have good specificity and sensitivity and reliable in prognosticating the outcome in open injuries of the tibia.